Designing from the dumpster: experiences of developing products using discards. (2017) - Ordoñez, Isabel; Rexfelt, Oskar
This article presents results from the waste to design (W2D) project, which analysed six product development thesis projects that were carried out to make use of specific waste materials. The W2D project investigated the challenges faced when designing with waste and how these can be addressed. A need was found for a pre-process, where material properties are analysed, several possible application areas are suggested and screening is subsequently performed to determine which product type to develop. The main challenge observed was the lack of reliable material property data for the discarded materials, which hindered well-informed screening. Understanding the processes needed for designing with waste is a first step in facilitating this work in the future.